LEGITIMACY AS A LIMITING FACTOR OF POLITICAL UTILITY OF MILITARY POWER - Milenković, Miloš; Vračar, Milinko (Serbian political thought, 2023)
Resume In the post-Cold War era, determined by the strong influences of globalization and the information revolution, it can be seen that military power fails to produce the expected political effects or at least those effects that could be produced in the past. One of the reasons why is that so, the authors find in the deficit of its legitimacy. The legitimacy deficit is discussed in the paper from three aspects.First, the legitimacy of the use of force is seen in the paper through the attitude of public opinion towards the use of force. In this sense, the sensitivity of public opinion to human casualties and destruction is expected. However, the authors note that today the quality of life has become the new vital value of the nation, which is reflected in the reduced willingness of citizens to give up their acquired rights and comfort of life. The willingness of the population to make the sacrifice that the use of force entails is a measure of the legitimacy of military power.Second, the authors point to the legality of the use of force as a source of its legitimacy. The legality of the use of force is viewed through internal and international law. Likely, the use of force that is contrary to internal and/or international law will be in a legitimacy deficit. By pointing out the illegal use of force, the military action itself is being de-legitimized and mobilizes public opinion resistance to such an act.And thirdly, the paper analyzes how the type and character of war determines its legitimacy. It is closely related to the question of the justification of starting a war and the existence of a "just aim" of war, but also to the question of how and by what means the war is waged. The authors also point to the misuse of the term "humanitarian intervention", which is used to provide legitimacy to military action, most often aggression.Considering the influence of legitimacy issues on the effectiveness of the use of force, the authors conclude that the success of states in imposing their own will on the opponent is no longer primarily based on their military power, at least not to the extent that it was before. Much more important today is the determination and ability of the state to combine military power with other types of national power. Only in this way will it be possible to turn a military victory in the war into a political victory, which should ensure an acceptable and long-term sustainable peace.
Keywords: military power; legitimacy; public opinion, type and character of war; smart power